2020
DOI: 10.3390/ani10061091
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions and Milk Fatty Acid Profiles in Dairy Cows Fed Linseed, Measured at the Group Level in a Naturally Ventilated Housing and Individually in Respiration Chambers

Abstract: The present study evaluated the effects of linseed supplementation on CH4 emission and milk fatty acid composition in dairy cows measured at the group level in an experimental dairy loose housing using a tracer gas technique and individually in tied stalls and respiration chambers. Cows (2 × 20) were maintained in two separate sections under loose-housing conditions and received a diet supplemented with extruded linseed (L) lipids (29 g·kg−1 dry matter) or a control (C) diet containing corn flour. Subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
3
12
1
Order By: Relevance
“…In another study, Martin et al [ 38 ] evaluated the effects of adding crude linseed, extruded linseed, or linseed oil to a control diet on methane production in dairy cows. In contrast to Poteko et al [ 40 ], Martin et al [ 38 ] found that all treatment diets significantly reduced daily CH 4 emissions, but to different extents (−12% with crude linseed, −38% with extruded linseed, −64% with linseed oil) compared with the control diet. The same ranking among diets was observed for CH 4 as a percentage of energy intake or grams of CH 4 per kilograms of OM intake.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In another study, Martin et al [ 38 ] evaluated the effects of adding crude linseed, extruded linseed, or linseed oil to a control diet on methane production in dairy cows. In contrast to Poteko et al [ 40 ], Martin et al [ 38 ] found that all treatment diets significantly reduced daily CH 4 emissions, but to different extents (−12% with crude linseed, −38% with extruded linseed, −64% with linseed oil) compared with the control diet. The same ranking among diets was observed for CH 4 as a percentage of energy intake or grams of CH 4 per kilograms of OM intake.…”
Section: Discussionmentioning
confidence: 73%
“…More studies were conducted regarding the use of linseed, mostly in lactating cows [ 7 , 38 , 39 , 40 ], whereas few studies [ 3 , 41 , 42 ] evaluated linseed in goat diets with variable inclusion levels. In particular, Bernard et al [ 41 ] used an amount of extruded linseed of about 22% on DM, which is a much higher level than that tested in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetable oils and the LCC contained in them are shown to have positive effects in livestock growth [ 25 , 26 ], while MCC can be used in low doses to inactivate pathogens in feed and improve swine health and performance [ 27 ]. Both LCC and MCC can be used as natural alternatives to antibiotics [ 26 , 27 ] and for methane mitigation in cattle [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation strategies have been proposed at the farm scale [5] in order to reduce the environmental impact of milk production from dairy cows, including: housing system type [6]; different floor type and manure handling systems [7,8]; application of urease inhibitors [9]; application of processing residues in the coffee industry on manure [10]; combinations of techniques (e.g., floor system and cleaning, floor system and manure acidification) [11], and increased production efficiency at an animal level though genetics, feeding management and nutrition [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%